Crucial role of TRPC1 and TRPC4 in cystitis-induced neuronal sprouting and bladder overactivity - Boudes, Mathieu; Uvin, Pieter; Pinto, Silvia; Freichel, Marc; Birnbaumer, Lutz; Voets, Thomas; Ridder, Dirk De; Vennekens, Rudi (PLOS ONE, 2013)
Purpose During cystitis, increased innervation of the bladder by sensory nerves may contribute to bladder overactivity and pain. The mechanisms whereby cystitis leads to hyperinnervation of the bladder are, however, poorly understood. Since TRP channels have been implicated in the guidance of growth cones and survival of neurons, we investigated their involvement in the increases in bladder innervation and bladder activity in rodent models of cystitis. Materials and Methods To induce bladder hyperactivity, we chronically injected cyclophosphamide in rats and mice. All experiments were performed a week later. We used quantitative transcriptional analysis and immunohistochemistry to determine TRP channel expression on retrolabelled bladder sensory neurons. To assess bladder function and referred hyperalgesia, urodynamic analysis, detrusor strip contractility and Von Frey filament experiments were done in wild type and knock-out mice. Results Repeated cyclophosphamide injections induce a specific increase in the expression of TRPC1 and TRPC4 in bladder-innervating sensory neurons and the sprouting of sensory fibers in the bladder mucosa. Interestingly, cyclophosphamide-treated Trpc1/c4−/− mice no longer exhibited increased bladder innervations, and, concomitantly, the development of bladder overactivity was diminished in these mice. We did not observe a difference neither in bladder contraction features of double knock-out animals nor in cyclophosphamide-induced referred pain behavior. Conclusions Collectively, our data suggest that TRPC1 and TRPC4 are involved in the sprouting of sensory neurons following bladder cystitis, which leads to overactive bladder disease.